Transitional metal/chalcogen dependant interactions of hairpin DNA with transition metal dichalcogenides, MX2 - Loo, Adeline Huiling (2015)
Owing to the attractive properties that transition metal dichalcogenides (TMDs) display, they have found recent application in the fabrication of biosensing devices. These devices involve the immobilization of a recognition element such as DNA onto the surface of TMDs. Therefore, it is imperative to examine the interactions between TMDs and DNA. Herein, we explore the effect of different transition metals (Mo and W) and chalcogens (S and Se) on the interactions between hairpin DNA and TMDs of both bulk and t-BuLi exfoliated forms. We discovered that the interactions are strongly dependent on the metal/chalcogen composition in TMDs.